New species of microfungi from Brazilian Amazon rainforests - Monteiro, Josiane Santana; Carmo, Luana Teixeira do; Fiúza, Patrícia Oliveira; Paiva Ottoni, Bianca Maíra de; Pascholati Gusmão, Luís F.; Casta?eda-Ruiz, R. F. (Mycotaxon, 2014)
Isthmophragmospora laevispora sp. nov., Henicospora amazonensis sp. nov., and Sporidesmiella curtiphora sp. nov. found on submerged decaying plant materials are described and illustrated. Isthmophragmospora laevispora is distinguished by smooth pale brown conidia, each composed of two unequal 2-septate bodies connected by a cellular isthmus; H. amazonensis is characterized by clavate to pyriform, 3-4-septate, 1-2 distoseptate, smooth, pale golden brown conidia; and S. curtiphora has obovoid to lamp-shaped, 1-septate, olivaceous-brown conidia. © 2014. Mycotaxon, Ltd.